Manajemen Kepemimpinan dalam Mengetahui Kualitas Kerja Pegawai di Kantor Urusan Agama (KUA) Kecamatan Maron Kabupaten Probolinggo - Chairul Yakin; Mochammad Dawud (Icon: Islamic Communication and Contemporary Media Studies, 2022)
Leadership management is one of the very important components in leadership in an institution. As a leader, his existence is very much needed, because it is closely related to the way he leads (leadership). The focus of the problems studied in this thesis is: 1) How is the management of the leadership of KUA Maron District, Probolinggo Regency? 2) What are the supporting and inhibiting factors in leadership management in KUA Maron District, Probolinggo Regency?. 3) What is the quality of work of employees in KUA Maron District, Probolinggo Regency?. The purpose of this study is to find out how the leadership management used by the head of KUA Maron District, Probolinggo Regency in improving the quality of employee work. Qualitative-descriptive research methods. The subjects of the study used purposive sampling techniques. Data collection techniques use interviews, observations and documentation. This research obtained the results that Leadership Management in knowing the Quality of Work of Employees in KUA Maron District, Probolinggo Regency, is: Using the principles of leadership management Uswatun Hasanah, recognizing and distributing work according to the potential of each employee, establishing good communication and cooperation with employees, providing motivation and work assistance to employees. The Quality of Work of Employees in KUA Maron District, Probolinggo Regency is fairly effective. This is evidenced by: Employees perform work in accordance with their respective duties and functions, work on time or discipline, the existence of shoulder to shoulder or cooperate with each other, effective communication, increasing the potential of each employee.